The Cover of Religious Tolerance for Indonesian Society in Digital News Media and World Peace - Putri, Erita (Jurnal komunikan, 2025)
The face of religious tolerance is a form of society in Indonesia where people of different religions, cultures and ethnicities live together with each other. It is practised by the Indonesian people as a way of life and is enshrined as the foundation of the Indonesian state, Bhinneka Tunggal Ika. It is always interesting, both as positive and negative news, for the media to cover the manifestation of religious tolerance. In the sociology of religion, it is possible to consider online media as a phenomenon of positive pluralism, as they show religious interaction in a multireligious, multiethnic and multiracial social setting. The news content presented to the public, whether designed by media teams or not, will influence each public perspective and direct the context of public thinking in seeing Buddhist monks performing the Thudong ritual by walking from Thailand to the Borobudur temple in Indonesia, so that the Indonesian people welcome them very enthusiastically and the monks can celebrate their Vesak day well. The approach of descriptive qualitative method of religious tolerance in the description of the face of religious tolerance in Indonesian society, especially in the commemoration of the implementation of the Thudong ritual performed by Buddhist monks and reported in the mass media.